Development of Automatic Tube Oil Skimmer. Issue 1 (August 2020) - Vignesh, T; Bhuvaneswari, M; Manojkumar, S.; Kishore, S.; Bommuraj, N.
Abstract: The paper work represent the removing oil from the water which is wasted from the machines. The machines get more heated while running, oil and water is used to cool the machine. This investigations is removing oil from water surface is done by skimmer. The oil skimmer is having tube under different operation condition (thickness of oil film, temperature of oil, rotational speed of tube, water PH, oil tube and tube material tube). The oil skimmer has floating tube with fixed length, flexible and discrete segmented model. The design of the wheel according to the tube size and tube length is fixed according to the tank size. Wheel is connected with the belt which is immersed in the oil and water mixer tank. While running the pulley wheel belt is coming upper, the wiper is attached in the frame. Wiper removes the oil coming from the belt. This method is most efficient method to solve the human fatigue and cost effective method.